(untitled) (Scientific journal of the Fergana State University, 2026)
This article is about translations of comparative images in the test of “Baburname”. It is devoted to solve some problems to translate comparative description in classical literature. We know “Baburname” is historical, biographical, scientific and adventurous novel that’s why it has some issue to translate them.